2016
DOI: 10.1097/bot.0000000000000473
|View full text |Cite
|
Sign up to set email alerts
|

Crossed Wires Versus 2 Lateral Wires in Management of Supracondylar Fracture of the Humerus in Children in the Hands of Junior Trainees

Abstract: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 19 publications
(17 reference statements)
1
16
0
1
Order By: Relevance
“…However, the crossed entry fixation method has been shown to have a higher risk of iatrogenic ulnar nerve injury than the lateral entry method [ 43 ]. Some studies reported that the risk of iatrogenic ulnar nerve injury could be greatly reduced through the placement of a medial pin with a medial mini-incision on the medial epicondyle and the extension of the elbow [ 8 , 26 , 31 , 33 ]. The risk of iatrogenic ulnar nerve injury associated with medial pin entry could be resolved after wound exploration and placement of the medial pin at a new location.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the crossed entry fixation method has been shown to have a higher risk of iatrogenic ulnar nerve injury than the lateral entry method [ 43 ]. Some studies reported that the risk of iatrogenic ulnar nerve injury could be greatly reduced through the placement of a medial pin with a medial mini-incision on the medial epicondyle and the extension of the elbow [ 8 , 26 , 31 , 33 ]. The risk of iatrogenic ulnar nerve injury associated with medial pin entry could be resolved after wound exploration and placement of the medial pin at a new location.…”
Section: Discussionmentioning
confidence: 99%
“…In four studies in which children with SCHF were treated with crossed pinning with a mini-open incision [ 8 , 26 , 31 , 33 ], the risk of iatrogenic ulnar nerve injury between the children treated with lateral pinning entry and the children treated with crossed pinning with mini-open incisions was not different (RR = 1.58, 95% CI 0.008–29.57, P = 0.76) (Fig. 4 B).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Crossed-pin constructs were significantly more stable in extension, internal rotation, and external rotation, as well as more stable compared with both lateral pin constructs. In a single-center, prospective randomized controlled trial, Abdel Karim et al [ 20 ] assigned 60 pediatric patients with operatively treated SCH fractures to receive either 2 lateral pin constructs or a 2 crossed-pin construct. The authors found a significantly higher rate of reduction loss when using 2 lateral pins (20%) compared with 2 crossed pins (0%) ( P = .031).…”
Section: Discussionmentioning
confidence: 99%